Distribusi Ukuran, Pola Pertumbuhan, dan Faktor Kondisi Ikan Endemik Opudi (Telmatherina prognatha) di Danau Matano, Sulawesi Selatan - Andi Chadijah; Sulistiono Sulistiono; Gadis Sri Haryani; Ridwan Affandi; Ali Mashar (Institut Pertanian Bogor, 2019)
Opudi fish (Telmatherina prognatha) is an endemic fish that live in the Lake Matano. Growth pattern of Telmatherina prognatha is very important to be studied for species conservation and management effort. This study aimed to analyze size distribution, growth pattern and condition factors of the fish as a basic information for fish resources management at Lake Matano. The study was conducted from March to August 2018 on six sampling locations. The fish sampling was carried out using multifilament nets with 0.5 inches in mesh size (30 m length and 2 m width) in the lake. The caught fishes were measured for total length and weight for growth analysis. The total of fish (n=853 individuals) consisted of male (483 individuals) and female (370 individuals). Total length (TL) of the fish ranged between 36.46-64.09 mm (mean 51.73±4,74mm) for male and 32.93-66.20 mm (mean 49.81±5.31 mm) for female fish. The growth patterns (length-weight relationships) of male and female fish were W=0.0004L2,5995 and W=0.0006L2,4875, indicating negative allometric growth patterns, respectively. Range condition factors in average were various and 0.9864±0.2084 in average for male and 1.0121±0.1571 for female, respectively, with quite high values on June 2018.